Semiotics Analysis The Art Work By Aliansyah Chaniago Entitled Lanscape Of Barus - Hismanto, Andi (Universitas Ciputra, 2019)
The art works have visual and verbal symbols signifying language phenomena. Art works such as paintings can also be called sign phenomena. The sign or symbol used by artists in creating a painting is the process of contemplation, feeling and artists' thoughts about the environment. The art installation by Aliansyah Chaniago entitled